Freshwater Sordariomycetes: new species and new records in Pleurotheciaceae, Pleurotheciales - Shi, Lin; Yang, Hao; Hyde, Kevin D.; Wijayawardene, Nalin N.; Wang, Gen-Nuo; Yu, Xian-Dong; Zhang, Huang (Phytotaxa, 2021)
Eight freshwater asexual strains collected from China and Thailand were subjected to morpho-molecular analyses. BLAST search results showed that the new strains belonged to Pleurotheciales, Sordariomycetes. Phylogenetic analyses based on a combined LSU, SSU, ITS and RPB2 sequence dataset are used to clarify the placement of the new strains within Pleurotheciales. Pleurothecium guttulatum and Pleurotheciella sympodia are introduced as two new species from freshwater habitats. New geographical record of Pleurotheciella nilotica from Asia (Thailand and China) is reported. New habitat and geographical records of Phaeoisaria annesophieae (from freshwater habitats in Asia) are reported. Descriptions and illustrations of the new species and records, as well as known species Rhexoacrodictys erecta and Phaeoisaria annesophieae, are provided. A key to Pleurotheciella species is provided.